Fabrication of graphene oxide scrolls and other architectures - Wu, Jumiati (2015)
Graphene, a two-dimensional material made of entirely carbon atom in sp2 hybridization has been introduced in 2004. Due to its unique and excellent electrical, mechanical and optical properties, graphene is popularly researched as materials of interest to be used in variety of applications. As a two-dimensional material, graphene is considered as building block for other carbon based materials. Graphene can wrap around itself and form buckyballs, roll to form carbon nanotube (CNT), and stack to form graphite. All these different architectures of carbon materials result in distinctive properties. Hence, it is exciting to fabricate new architectures based on carbon materials. Novel graphene architecture such as carbon nanoscroll or graphene scroll is recently reported. This architecture is similar to CNT. Both of them are made of rolled graphene. However, CNT displays a closed cap configuration while carbon nanoscroll or graphene scroll shows an open cap configuration. Molecular combing is applied on two-dimensional material of GO sheets for the first time. Molecular combing of GO sheets in aqueous solution is executed on various hydrophobic substrates which consequently results in formation of GO scrolls. The obtained GO scroll is then characterized by using optical microscopy, Raman spectroscopy, atomic force microscopy (AFM) and transmission electron microscopy (TEM). Molecular combing technique has produced aligned individual GO scrolls with high density easily. The successful fabrication of GO scroll is found to be controlled by the substrate's hydrophobicity as well as water which was the solvent of GO sheet solution. A device based on a single reduced GO scroll is produced with gold as electrodes and further utilized as NO2 gas sensor. As an active material, rGO scroll has demonstrated the ability to detect NO2 as low as 0.4 ppm with detection limit of 56 ppb. Micro-contact printing of hydrophilic 16-mercaptohexadecanoic acid (MHA) on Au substrate followed by passivation of hydrophobic 1-octadecanethiol (ODT) revealed the hydrophilic-hydrophobic region. By performing molecular combing of GO sheets on hydrophilic-hydrophobic patterned substrates, novel GO architecture is observed. Molecular combing on MHA dot-patterned substrate results in the beaded GO string, which is characterized by optical microscopy, scanning electron microscopy (SEM), AFM, Raman spectroscopy and TEM. The resulting GO architecture can be easily tuned by controlling the size and shape of hydrophilic region. Moreover, GO sheets has also been demonstrated to favor hydrophilic area and thus selectively reside and adopt hydrophilic area size and shape, such as line and cross pattern. The concentration of GO sheets and molecular combing speed are two factors to tune the density of resulting beaded GO strings. In addition, the size of GO sheets is also crucial to the formation of beaded GO string. The single beaded rGO string based device is also fabricated, which gives better NO2 gas detection limit (5.8 ppb). In addition, the GO scroll mesh is produced by stacking high density GO scrolls which are aligned in vertical and horizontal directions. Vertically aligned GO scrolls are stacked on horizontally aligned GO scrolls by using two-dimensional material transfer method. The resulting GO scroll mesh is shown to be made of well-connected GO scrolls in large area as characterized by optical microscopy, Raman spectroscopy and AFM. The GO/rGO scroll mesh is structurally stable and therefore transferrable onto flexible substrates such as PET. Optical transparency and sheet resistance of GO/rGO scroll mesh are excellent due to its mesh/network structure and the conductivity of rGO. The rGO scroll mesh based device is fabricated, which shows remarkable electrical stability with multiple bending tests.